Analysis of the Influence of Product Quality on Purchasing Decisions at PT. W Standard Indonesia - Belianus Patria Latuheru; Dedik Wiryawan; Farida Yani; Riny Jefri; Dicky Jhon Anderson Butarbutar (Budapest International Research and Critics University, 2022)
In recent years, advances in the automotive world, especially motorcycle, have grown and developed rapidly, this has made almost everyone around the world want and need a motorcycle with good performance and quality and a stable resale price. PT. W Standard Indonesia is a distributor of various types of motorcycle spare parts under the W Standard brand which is located in Medan City. This study aims to determine and analysis of the influence of product quality on purchasing decisions at PT. W Standard Indonesia. This type of research is descriptive quantitative research. The population in this study is the number of customers of PT. W Standard Indonesia in the last three months as many as 102 people. The number of samples for this study is 50 customers. The data analysis method used descriptive statistics and simple linear regression analysis consisting of partial test (t) and coefficient of determination (R2). The results show that product quality has positive and significant effect on purchasing decisions at PT. W Standard Indonesia. Product quality can explain purchasing decisions at PT. W Standard Indonesia by 13.6% and the remaining 86.4% is explain by other variables not examined in this study.